Changes in Nutritional Status of Hospitalized Patient in a Tertiary Level Hospital (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Nutrition is an important health parameter among hospital admitted patients. The objective of our study was to evaluate the changes of nutritional status among the adult patients   during hospitalization.Materials and methods: It is prospective observational study done on 100 patients admitted at Medicine ward, CMCH from January 2012 to June 2012. 100. Body Mass Index (BMI) and Mid Arm Circumference (MAC) were compared at the time of admission and at weekly interval and hospital discharge. Data was collected and analyzed by SPSS 20.Results: Among the 100 patients 52(52%) were male and 48(48%) were female.38 (38%) patients had BMI